2017
DOI: 10.1146/annurev-immunol-051116-052350
|View full text |Cite
|
Sign up to set email alerts
|

Th2 Cells in Health and Disease

Abstract: Helper T (Th) cell subsets direct immune responses by producing signature cytokines. Th2 cells produce IL-4, IL-5, and IL-13, which are important in humoral immunity and protection from helminth infection and are central to the pathogenesis of many allergic inflammatory diseases. Molecular analysis of Th2 cell differentiation and maintenance of function has led to recent discoveries that have refined our understanding of Th2 cell biology. Epigenetic regulation of Gata3 expression by chromatin remodeling comple… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
261
1
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 303 publications
(278 citation statements)
references
References 217 publications
8
261
1
1
Order By: Relevance
“…The detailed mechanisms underlying the GATA3-dependent regulation of its target genes are described in Section 5. [3,[43][44][45][46]. PcG and TrxG proteins were originally identiied in Drosophila; however, they also play essential roles in controlling mammalian gene expression in various normal and tumor tissues.…”
Section: Gata3 Plays Roles In Various Tissues As Well As the Immune Smentioning
confidence: 99%
See 4 more Smart Citations
“…The detailed mechanisms underlying the GATA3-dependent regulation of its target genes are described in Section 5. [3,[43][44][45][46]. PcG and TrxG proteins were originally identiied in Drosophila; however, they also play essential roles in controlling mammalian gene expression in various normal and tumor tissues.…”
Section: Gata3 Plays Roles In Various Tissues As Well As the Immune Smentioning
confidence: 99%
“…This study showed that a binding patern in which Ezh2 binds upstream and Menin binds downstream of the transcription start site was frequently found at highly expressed genes, and a binding patern in which Ezh2 and Menin bind to opposite positions was frequently found at low-expressed genes in T lymphocytes. Interestingly, genes showing a binding patern in which Ezh2 and Menin occupied the same position displayed greatly enhanced sensitivity to Ezh2 deletion [3,58].…”
Section: Spatial Interplay Between Polycomb and Trithorax Complexesmentioning
confidence: 99%
See 3 more Smart Citations